Vibration suppression of flexible beam using electromagnetic shunt damper - Ariffin, Abdullah (2013)
In this thesis, the electromagnetic shunt damper was newly developed to passively suppress the vibration of the flexible cantilever beams. The electromagnetic shunt damper, which is electro-mechanically coupled with the flexible structures, simply consists of a coil, a permanent magnet, and an R-L-C circuit. The ends of the conductive coil are connected to the R-L-C series shunt circuit and the battery as well. The aim of electronic magnetic shunt damper is to achieve the damping effect. This effect is affected by the position of the conductor and magnet. The data was record by using the DAQ cable and Accelerometer. The position of the magnet which is at the bottom of the coil does not able to induce the damping effect. Since then it has been replaced by spherical conductor by placed inside the coil. Present results show that the electromagnetic shunt damper can be successfully applied to reduce the vibration of the flexible structures. The vibration and damping characteristics of the flexible beams with the electromagnetic shunt damper were investigated by tuning the circuit parameters. The change in value of resistor, voltage, and capacitor were investigated towards the effect of damping characteristic. There are four different of resistor, three different of voltage, and three different of capacitors were employed to study this effect. The vibration of the flexible beam was reduced most with R= 1.5 Ohm, V= 9V, C = 2000 µF. With this tuning, the vibration of the flexible beam was reducing up to 91.6%. The data will be more significant if the disturbance employed on the aluminium plate in harmonic motions. This can achieve by using Mechanical Shaker machine. The magnet can use to induce the eddy current if the position magnet is placed inside the coil.